The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1021/jo502564w
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Diazaiptycenes: Materials for Solution-Processed Organic Electronics

Abstract: The synthesis and characterization of soluble azaiptycenes is reported. Optical and physical properties were studied and compared with those of the structurally consanguine azaacenes. Electrochemical experiments and quantum-chemical calculations revealed the electronic structure of the iptycene derivatives. Their crystallization behavior was examined. A highly fluorescent amorphous diazatetracene derivative was integrated into a simple organic light-emitting diode, showing enhanced performance compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
72
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 26 publications
0
72
0
3
Order By: Relevance
“…We demonstrated that triptycene‐carrying diazatetracenes are efficient emitters in organic light‐emitting diodes (OLEDs), increasing the diode's brightness by a factor of more than 200. The effect is likely due to the inhibition of crystallization . While for OLEDs this amorphization is critical, the same might be true for organic photovoltaic devices (OPVs).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated that triptycene‐carrying diazatetracenes are efficient emitters in organic light‐emitting diodes (OLEDs), increasing the diode's brightness by a factor of more than 200. The effect is likely due to the inhibition of crystallization . While for OLEDs this amorphization is critical, the same might be true for organic photovoltaic devices (OPVs).…”
Section: Introductionmentioning
confidence: 99%
“…6,13‐Bis((triisopropylsilyl)ethynyl)‐5,7,12,14‐tetraazapentacene (TAP; 2 ) forms crystalline films with excellent electron mobilities, however, the direct synthesis of TAP by using the diamine 1 in a condensation with simple ortho ‐quinones or dihalobenzenes (Pd catalyzed) remains challenging (Scheme ), and 2 is typically prepared via the intermediate 5 , followed by its oxidation into 6 and subsequent alkynylation. In contrast, the condensation of stable triptycene‐2,3‐dione with alkynylated diamines is efficient and leads to azaiptycenes in high yields (Scheme ) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The most frequently used reactions to construct such π-extended triptycenes are condensation reactions, e.g. of diketones with diamine moieties.…”
mentioning
confidence: 99%
“…, 7.19 (dd, J = 8.8, 2.5 Hz, 6H,10',3,6,14,17), 6.18 (s, 2H, bridgehead-H), 4.02 (s, 18H, OCH 3 ) ppm; 13 C NMR (151 MHz, C 2 D 2 Cl 4 ): δ 158.2 (C…”
mentioning
confidence: 99%